Bronchogenic Cyst in a 13 month Old Child - Shanza Nazish, Shanza Nazish; Uzma Aftab, Saima Ahsan, Tanveer Hussain Chaudhary, Abdul Hafeez Soomro, Muhammad Sabir Khan, Uzma Aftab , Saima Ahsan, Tanveer Hussain Chaudhary, Abdul Hafeez Soomro, Muhammad Sabir Khan (Journal of Rawalpindi Medical College, 2022)
Background Persistent cough ,stridor and respiratory distress are most common symptoms encountered by paediatrician in their daily practices.Although bronchogenic cyst is rare cause of persistent cough but should always be kept in differential diagnosis of respiratory sypmptoms nonresponding to antibiotics and bronchodilators. Case presentation 13 month old baby had history of frequent visits at hospital and treated as case of pneumonia and hyperreactive airway disease.Chest X-ray revealed cystic mass in mediastinum with CT chest confirmed bronchogenic cyst for which patient underwent surgical excision.Histopathology report revealed bronchogenic cyst .After surgical excision patient got stable with stridor got settled. Conclusion Case is being reported to create awareness related to bronchogenic cyst as cause of persistent cough and respiratory distress